Antidiabetic and antihyperlipidemic activities of extracts of Barleria cuspidata Heyne ex Nees on streptozotocin induced diabetic rats - Manohar Reddy; Raja Sundararajan (International Journal of Research in Pharmaceutical Sciences, 2021)
Traditionally, Barleria cuspidata Heyne ex Nees is utilized for antidiabetic action with the absence of logical investigation. Thus, the current examination was attempted to explore for its antidiabetic and antihyperlipidemic movement in streptozotocin instigated diabetic animal models. Blood glucose levels were estimated in normoglycemic rats at initial, 60th and 120th minutes intervals and in glucose feed hyperglycemic rats at initial, 30, 60, 90 and 120 minutes after a solitary portion of streptozotocin at 55 mg/kg body weight intraperitoneal were made diabetic in albino rats. Blood glucose levels were estimated at week by week spans after everyday administration of chloroform and methanol extracts of Barleria cuspidata at dosages of 250 and 500 mg/kg body weight. Other biochemical boundaries of serum triglycerides, cholesterol, HDL-cholesterol, LDL-cholesterol, VLDL-cholesterol, total protein, albumin, globulin, uric acid, creatinine, urea, transaminases, alkaline phosphatase, alanine aminotransaminase, insulin and glycosylated hemoglobin were like- wise estimated toward the finish of the investigation. Chloroform and methanol extracts of Barleria cuspidata by an oral organization for 21 days altogether (P<0.001) decreases the elevated blood glucose extents in diabetic rats whereas in normoglycemic rats it doesn’t adjust the blood glucose amounts altogether and in glucose feed hyperglycemic rats significantly decreases the raised blood glucose levels. Likewise, the chloroform and methanol extracts of Barleria cuspidata improved other biochemical boundaries related to diabetes. Moreover, the extracts of Barleria cuspidata favourable affect the histopathological changes of pancreas in streptozotocin initiated diabetic rats.